Disorders of Ejaculation: An AUA/SMSNA Guideline. Issue 3 (28th March 2022) - Shindel, Alan W.; Althof, Stanley E.; Carrier, Serge; Chou, Roger; McMahon, Chris G.; Mulhall, John P.; Paduch, Darius A.; Pastuszak, Alexander W.; Rowland, David; Tapscott, Ashley H.; Sharlip, Ira D.
Abstract : Purpose: Men who ejaculate before or shortly after penetration, without a sense of control, and who experience distress related to this condition may be diagnosed with premature ejaculation (PE), while men who experience difficulty achieving sexual climax may be diagnosed with delayed ejaculation (DE). The experience of many clinicians suggest that these problems are not rare and can be a source of considerable embarrassment and dissatisfaction for patients. The role of the clinician in managing PE and DE is to conduct appropriate investigation, to provide education, and to offer available treatments that are rational and based on sound scientific data. Materials and Methods: The systematic review utilized to inform this guideline was conducted by a methodology team at the Pacific Northwest Evidence–based Practice Center. A research librarian conducted searches in Ovid MEDLINE (1946 to March 1, 2019), the Cochrane Central Register of Controlled Trials (through January 2019) and the Cochrane Database of Systematic Reviews (through March 1, 2019). An update search was conducted on September 5, 2019. Database searches resulted in 1, 851 potentially relevant articles. After dual review of abstracts and titles, 223 systematic reviews and individual studies were selected for full-text dual review, and 8 systematic reviews and 59 individual studies were determined to meet inclusion criteria and were included in the review. Results: Several psychological health, behavioral, and pharmacotherapy options exist for both PE and DE; however, none of these pharmacotherapy options have achieved approval from the United States Food and Drug Administration and their use in the treatment of PE and DE is considered off-label. Conclusion: Disturbances of the timing of ejaculation can pose a substantial impediment to sexual enjoyment for men and their partners. The Panel recommends shared decision-making as fundamental in the management of disorders of ejaculation; involvement of sexual partner(s) in decision making, when possible, may allow for optimization of outcomes.